Nitric Oxide Production and Mononuclear Cell Nitric Oxide Synthase Activity in Malaria-Tolerant Papuan Adults - Boutlis, Craig S. (American Society for Microbiology, 2003)
Individuals living in regions of intense malaria transmission exhibit natural immunity that allows them to be without fever and other symptoms for most of the time despite frequent parasitization. Although this tolerance of parasitemia appears to be more effective in children than in adults (as evidenced by lower parasitemia fever thresholds with age), adults do exhibit a degree of tolerance but the mechanism(s) underlying this are unclear. Asymptomatic malaria-exposed children have higher levels of nitric oxide (NO) than children with severe disease, and NO has been proposed as a mediator of malarial tolerance. However, the ability of highly malaria-exposed asymptomatic adults to generate high-level basal NO is unknown, as is the relationship between NO and malaria tolerance in adults. The relationship between NO and malaria parasitemia was therefore determined in asymptomatic adults from Papua, Indonesia. Adults with Plasmodium falciparum parasitemia had markedly increased basal systemic NO production relative to aparasitemic Papuan controls, who in turn produced more NO than healthy controls from a region without malaria. Immunoglobulin E levels were universally elevated in malaria-exposed Papuan subjects, suggesting that the prevalence of intestinal parasitosis may be high and that nonmalarial infection may also contribute to high basal NO production. Basal peripheral blood mononuclear cell (PBMC) NO synthase activity was elevated in Papuans but poorly correlated with systemic NO production, suggesting that NO production in this setting arises not only from PBMCs but also from other tissue and cellular sources. NO production was associated with and may contribute to malaria tolerance in Papuan adults.